2010
DOI: 10.2176/nmc.50.421
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Metastasis From Follicular Thyroid Carcinoma -Two Case Reports-

Abstract: A 58-year-old woman and a 71-year-old woman presented with extremely rare skull base metastases from follicular thyroid carcinoma (FTC). Surgical removal and external radiotherapy were performed followed by iodine-131 ( 131 I) brachytherapy and thyroid hormone administration. The metastatic tumors in the skull base were well controlled. Treatment for skull base metastasis from FTC includes surgical debulking of the metastatic lesion, as well as complete resection of the thyroid gland, followed by internal irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The use of bisphosphonates for bone metastasis of thyroid carcinoma has been reported in only 2 patients [39, 67]. Administration of zoledronic acid and alendronate sodium hydrate decreased urinary type I collagen N-telopeptide, which indicated the suppression of bone resorption.…”
Section: Treatment Of Skull Base Metastasis From Ftc and Ptcmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bisphosphonates for bone metastasis of thyroid carcinoma has been reported in only 2 patients [39, 67]. Administration of zoledronic acid and alendronate sodium hydrate decreased urinary type I collagen N-telopeptide, which indicated the suppression of bone resorption.…”
Section: Treatment Of Skull Base Metastasis From Ftc and Ptcmentioning
confidence: 99%
“…The largest series of skull metastasis from thyroid carcinoma reported a frequency of only 2.5% among 473 patients [45]. Moreover, skull base metastasis from DTC is even rarer, with only 28 reported cases, including 18 cases of skull base metastasis from FTC [6, 7, 24, 30, 39, 44, 45, 49, 50, 54, 56, 57, 60, 63, 69, 70, 78] and 10 cases from PTC [4, 12, 20, 23, 34, 38, 64, 65, 77] (Table 2). In this review article, the clinicopathological and molecular histochemical features and treatment modalities of skull base metastasis of DTC, namely, FTC and PTC, are discussed with a review of literatures on molecular pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Among the patients with metastatic follicular thyroid cancer, 20% of metastases occur in bones, 5 but metastases to the skull are rare. 6 In this patient, a metastatic lesion in the posterior skull was “hidden” in the diagnostic 131 I scan by overlapping nose, and mouth activity. The normal patterns of radioiodine uptake in the nose, mouth, and salivary (parotid and submandibular) glands have been described and although there may be some differences due to pre-existing abnormalities and variation in uptake, the usual pattern includes focal nose and linear buccal mucosa activity.…”
Section: Discussionmentioning
confidence: 82%
“…Akira Matsuno et al [8], reviewed nineteen case reports published earlier and their case reports of two cases and concluded that the skull base metastasis is more common in females and the most common symptom due to skull base metastasis was cranial nerve palsy. This was also observed in our patient who had developed right sixth cranial nerve palsy causing diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the mainstay of treatment will be surgical removal of the primary in the thyroid along with lymph node metastasis and I-131 ablation if uptake is noted in the metastasis. If a cold nodule is noted on scintigraphy, external beam radiation will be the choice of treatment [8].…”
Section: Discussionmentioning
confidence: 99%